Family Ties and Organizational Design: Evidence from Chinese Private Firms - Cai, Hongbin; Li, Hongbin; Park, Albert; Zhou, Li-An (The Review of Economics and Statistics, 2013)
Analyzing data from a unique survey of managers of Chinese private firms, we investigate how family ties with firm heads affect managerial compensation and job assignment. We find that family managers earn higher salaries and receive more bonuses, hold higher positions, and are given more decision rights and job responsibilities than nonfamily managers in the same firm. However, family managers face weaker incentives than professional managers, as seen in the lower sensitivity of their bonuses to firm performance. Our findings are consistent with the predictions of a principal-agent model that incorporates family trust and endogenous job assignment decisions.